Addressing metastatic individuals everyday: Rationale and design of the nurse AMIE for Amazon Echo Show trial among metastatic breast cancer patients - Brett R. Gordon; Ling Qiu; Shawna E. Doerksen; Bethany Kanski; Abigail Lorenzo; Cristina I. Truica; Monali Vasekar; Ming Wang; Renate M. Winkels; Saeed Abdullah; Kathryn H. Schmitz (Contemporary Clinical Trials Communications, 2023)
Background: Metastatic Breast Cancer (MBC) patients often feel their symptom-related needs are unmet, despite visiting their doctors up to once a week. Novel approaches are needed to address symptoms without requiring additional appointments. Technology based symptom management approaches to address symptoms have not been well tested. Methods: Nurse AMIE (Addressing Metastatic Individuals Everyday) is a technology based supportive care platform that provides guideline-concordant symptom management interventions in response to patient reported symptoms. We have previously successfully implemented a tablet version of Nurse AMIE. However, some eligible patients chose not to participate because they were overwhelmed by the technology. To address this barrier, we translated the Nurse AMIE platform to the Amazon Echo Show, which allowed for voice-based interactions. Forty-two MBC patients were randomized 1:1 to receive the Nurse AMIE for Echo Show immediately for six months, or to receive the same intervention for three months, after a three month delay. The primary outcome was change in physical distress over three months, and secondary outcomes included feasibility, acceptability, patient reported outcomes and usability. Conclusions: Results from the Nurse AMIE for Echo Show trial will identify the feasibility, acceptability, and preliminary effects of the Nurse AMIE for Echo Show on patient reported outcomes. Untested novel technologies, particularly voice-based artificial intelligence devices may an effective and scalable vehicle through which we can deliver supportive care interventions. Clinicaltrials.gov identifier: NCT04673019.